Longterm effects of land clearing methods, tillage systemsand cropping systems on surface soil properties of a tropical Alfisol in S. W. Nigeria - Hulugalle, N. (Wiley, 1994)
The long‐term effects of land clearing methods (manual, shear blade, tree‐pusher/root‐rake combination, traditional), tillage systems (disc ploughing, mechanized no‐tillage, traditional) and cropping systems (annual cropping, alley cropping, graxed pasture) on surface soil physical and chemical properties were evaluated on an Alfisol in south‐western Nigeria ten years after land clearing. Long‐term soil physical degradation was greatest after mechanized land clearing or tillage systems. The erosion resulting from soil compaction with mechanized land management systems resulted in exposure of subsoil. Cropping system had no significant effect on soil physical properties. Alley cropping decreased exchangeable calcium and pH, and increased total acidity mainly through the greater demand for calcium by the hedgerow species. Grazed pasture depleted exchangeable potassium because it was taken up by the grass and exported from the site by the cattle following consumption of the grass.